Can citizen science help delimit the geographical distribution of a species? The case of the Callistoctopus sp. (“eastern octopus”) on the Brazilian coast - Jesus, Manuella Dultra de; Zapelini, Cleverson; Schiavetti, Alexandre (Ethnobiology and Conservation, 2021)
This study presents the first considerations and observations of the occurrence of the octopus Callistoctopus sp. on the coast of Brazil. Local ecological knowledge (LEK) and citizen science, used as a research tool, were fundamental to confirm the presence and delimit the distribution of this species on the Brazilian coast. In all, 187 interviews were conducted with octopus fishers in 17 localities surrounding six marine protected areas, between March 2018 and August 2019. During the development of the work, the number of volunteer participants significantly increased, from the initial 107 specialists to about 2180 local informants, including fishers, divers and diving instructors. The SWOT matrix was used as a synthesis method to identify the possibilities for the use of citizen science in ethnoecological studies. By using citizen science, it was possible to extend the area of distribution of this new species from the three existing records of individuals captured for the state of Pernambuco and Bahia to eleven records for more than seven states. The citizen science tool was considered useful for the generation of data that complement scientific research, and its greatest obstacle for use in ethnobiological studies was the need to motivate volunteers to increase the robustness of the collected data.